Associations between non-suicidal self-injury and experiential avoidance: A systematic review and Robust Bayesian Meta-analysis - Haywood, Sophie B.; Hasking, Penelope; Boyes, Mark (2023)
Objectives: Non-suicidal self-injury (NSSI) is the intentional and deliberate damage to an individual's own body tissue without the intent to suicide. Individuals who have higher self-reported levels of experiential avoidance are more likely to report a history of NSSI. The current study systematically reviewed the literature and meta-analysed studies assessing associations between experiential avoidance and self-injury. Method: An extensive review was conducted of several databases (including ProQuest, Joanna Briggs, Web of Science, PsychArticles, PubMed, Scopus, and Ovid). Nineteen articles (two dissertations) met the inclusion criteria for the systematic review and 14 were analysed in a Robust Bayesian Meta-analysis. This review was registered through PROSPERO (CRD42020198041). Results: There was a small to medium, pooled effect size (d = 0.48, 95 % Credibility Interval 0.00–0.85). There was strong evidence for this effect size (Bayes Factor = 12.16), although there was considerable heterogeneity between studies (τ =0.68, 95 % CI [0.44, 0.1.05]). The analysis testing whether these findings may be due to publication bias was inconclusive (Bayes Factor = 2.45). Limitations: The majority of studies included were cross-sectional, in English, and most studies were of university students. While some studies reported on recency/frequency of NSSI there was not enough data to conduct meta-analysis. Conclusion: These results suggest there is a robust association between history of NSSI and experiential avoidance. However, as most studies operationalise avoidance as a unidimensional construct, it is not clear which aspects of avoidance differentiate individuals with and without a history of NSSI.